Educational support for disadvantaged students in Vietnamese higher education - Quoc Cuong Nguyen Dinh; Van Vu Hong (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study aims to examine how social inequality is shaped; to determine the scope and evaluate the effectiveness of educational support programs for disadvantaged students in Vietnamese higher education. The study employs a mixed-methods design, combining document analysis, a questionnaire survey with 227 participants from 10 universities, and semi-structured interviews with 16 administrators, faculty members, and students. Quantitative data were processed using descriptive statistics, while qualitative data were analyzed thematically to clarify educational institutions’ practices and implementation gaps. The results show that support activities remain primarily focused on scholarships and financial aid, while academic support, psychological counseling, and capacity-building services are fragmented and not fully integrated into the management systems of higher education institutions. The study also indicates that inequality exists not only through economic disadvantage but also through deficiencies in cultural capital, learning skills, social support, and access to educational resources. From a theoretical perspective, the findings further clarify the theory of social reproduction and equity-oriented educational governance by showing that inequality is also reproduced through fragmented support governance. The conclusion is that support for disadvantaged students needs to be managed as an integrated, multidimensional, and systemic equity mechanism, rather than as isolated welfare interventions.